2012
DOI: 10.1016/j.joca.2012.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic activity of subchondral bone during the progression of osteoarthritis in a rabbit anterior cruciate ligament transection model

Abstract: Angiogenic activity of subchondral bone was elevated in the early to progressive stage of OA and vascular invasion into the osteochondral junction followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
4
31
0
1
Order By: Relevance
“…Because the biomechanical instability (due to ACLT) is not corrected in this model, it was decided to focus on early degenerative changes that could be prevented by a single, early injection of Dex: this approach modelled the critical clinical window between an ACL tear and arthroscopic repair. However, less degenerative changes were observed macroscopically in the lateral femoral condyle cartilage than in the medial femoral condyles at 3 weeks post-ACLT, in agreement with previous observations made in this rabbit model (Le Graverand et al , 2002; Saito et al , 2012). Because only lateral condyles were used for histology, this reduced the ability to ascertain treatment effects on cartilage degeneration by histological scoring.…”
Section: Discussionsupporting
confidence: 92%
“…Because the biomechanical instability (due to ACLT) is not corrected in this model, it was decided to focus on early degenerative changes that could be prevented by a single, early injection of Dex: this approach modelled the critical clinical window between an ACL tear and arthroscopic repair. However, less degenerative changes were observed macroscopically in the lateral femoral condyle cartilage than in the medial femoral condyles at 3 weeks post-ACLT, in agreement with previous observations made in this rabbit model (Le Graverand et al , 2002; Saito et al , 2012). Because only lateral condyles were used for histology, this reduced the ability to ascertain treatment effects on cartilage degeneration by histological scoring.…”
Section: Discussionsupporting
confidence: 92%
“…In a longer study investigating tibial plateau changes, Issac et al (Isaac et al, 2010b) reported significant increases in fissuring and loss of GAG at 6 and 12 months. While not all of these models included ACL failure, outcomes from this impact-induced ACL failure model are in agreement with these previous studies (Saito et al, 2012; Makoto Yoshioka et al, 1996). Significant loss of GAG and an increase of surface fissuring were documented in the medial femur.…”
Section: Discussionsupporting
confidence: 89%
“…So, osteoarthritis is considered an OC disease and possibly bone dependent because of the inflammatory factors delivered by the vasculature present in the subchondral bone . Blood vessels from the subchondral bone invade the articular cartilage promoting the progression of osteoarthritis and forming osteophytes . However, hyaline healthy cartilage is avascular while subchondral bone is vascular.…”
Section: Discussionmentioning
confidence: 97%